Integrasi Literasi Ekonomi Dalam Kegiatan Market Day Untuk Menanamkan Kemandirian Dan Keterampilan Finansial Anak Usia Dini Di Tk Cerdas Sukorejo Kendal - Kurniyah Kurniyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to describe the implementation of economic literacy through Market Day activities in instilling independence and financial skills in early childhood students at TK Cerdas Sukorejo, Kendal. The research employs a qualitative phenomenological approach, with research subjects comprising teachers, students, and parents. Data were collected through observation, interviews, and documentation, and subsequently analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the Market Day activity successfully serves as a contextual learning medium that teaches the concepts of buying and selling, money management, teamwork, and communication. Children demonstrated an increase in self-confidence, basic counting abilities, and an understanding of monetary value. Supporting factors for this activity include the active involvement of teachers and parents, while the constraint identified is the varying levels of children's understanding of the concept of monetary value. This study recommends the integration of economy-based activities from an early age using enjoyable and participatory methods.